Ferrocene functionalized enantiomerically pure Schiff bases and their Zn(ii) and Pd(ii) complexes: a spectroscopic, crystallographic, electrochemical and computational investigation. (8th February 2022) - Celedón, Salvador; Hamon, Paul; Artigas, Vania; Fuentealba, Mauricio; Kahlal, Samia; Carrillo, David; Saillard, Jean-Yves; Hamon, Jean-René; Manzur, Carolina
Abstract : A combination of X-ray diffraction, IR, UV-vis and NMR spectroscopy together with computational methods was used to characterize and study the properties of the title compounds. Abstract : In this contribution, we describe the synthesis, spectroscopic and structural characterization, as well as the electrochemical behavior of a series of four chiral ferrocene-functionalized Schiff base compounds derived from enantiomerically pure (1 R, 2 R )-(−)-1, 2-diaminocyclohexane. The ferrocene enaminones 3 and 4 were obtained upon monocondensation of ferrocenoylacetone Fc–C(O)CH2 C(O)R (R = CH3, 1 ; 4-C6 H4 OH, 2 ; Fc = (η 5 -C5 H5 )Fe(η 5 -C5 H4 )) with one amino group of the primary diamine. The two bimetallic complexes 5 and 6 were prepared via a one-pot three-components template procedure involving half-unit 3, 4-methoxysalicylaldehyde and tetrahydrated zinc(ii ) nitrate for 5, and half-unit 4, 4-formyl-3-hydroxybenzoic acid and palladium(ii ) acetate for 6 . All the syntheses were carried out in refluxing ethanol and compounds 3–6 were isolated as thermally stable, air and moisture compatible colored solids in 71–83% yields. They were characterized by several analytical (EA, ESI-MS) and spectroscopic methods ( 1 H/ 13 C NMR, FT-IR, UV-vis), including the molecular structures of 3 and 4 that were unequivocally established by single crystal X-ray diffraction analyses. Both crystallize in the orthorhombic non-centrosymmetric space group P 21 21 21 with two ( R, R )-(−)-chiral carbon atoms in the structures. Cyclic voltammetry showed that the greatest anodic shifts (270 mV) of the ferrocenyl Fe(ii )/Fe(iii ) redox potentials are observed for the D-π-A push–pull derivative 6 . Beyond experimental characterization, DFT- and TDDFT-based theoretical analyses of the new chiral ferrocene-containing Schiff base complexes allow interpretation of their observed spectroscopic, structural and electronic features.